Isolation of Mycobacteriophage: Novel tool to treat Mycobacterium spp - Satish, R.; Desouza, A. (International Journal of Scientific Research in Biological Sciences, 2018)
Mycobacteriophages are viruses that infect Mycobacterium spp. To date,9666 mycobacteriophages have been isolated and 1519 mycobacteriophage genomes have been sequenced(phagesdb.org). The aim of this study was to isolate mycobacteriophages from different soil samples using Mycobacterium smegmatis as host. In this study mycobacteriophages have been isolated from 10 different soil samples. Presence of these phages was confirmed by qualitative plaque formation on plates. These 10 different phages were further tested for host diversity using M. fortuitum subsp. fortuitum MTCC993, Mycobacterium kansasiiMTCC3058, Mycobacterium aviumsubsp. avium MTCC1723 and Mycobacterium tuberculosis MTCC300. Three among these 10 phages, were found to infect all the 4 different species of Mycobacterium besides the host Mycobacterium smegmatis that was used for isolation of the phages. This truly reflects the host diversity of the phages and their ability to rapidly adapt to new hosts. These phages could also hold a great potential to be used as tools of genetic manipulation to study Mycobacteria. Their potential for the treatment and eradication of M. tuberculosis can also be studied further.